Service politics and sustainability performance for N27 constituency, Sarawak - Kipli, Nur Aida; Abdollah, Ida Izumi; Sadikin, Sarehan; Wan Achmed, Sharifah Shaneela (Faculty of Administrative Science and Policy Studies, 2023)
One of the major aims of this research paper is to identify factors determine the constituency’s performance achievements in the delivery of service politics in N27 Sebuyau, Kota Samarahan, Sarawak with a population of qualified voters for their constituency. The state constituency led by YB Datuk Hj Julaihi bin Hj Narawi from GPS (Gabungan Parti Sarawak) that formerly known as BN (Barisan Nasional/ National Front) from 1991 until present. His sustain support gained from his people since his last Sarawak State election encouraged researcher to conduct this study. Quantitative method was applied for the empirical outcomes. The findings of the research laid down the 8 determinant factors and 7 theme of analysis factors that contributed to his political sustainability performance and its influence N27 constituency's long-term success in preserving his position in the constituency through his service politics. The research also assesses the level of voter’s judgment on the existing quality of performance served by the constituency and satisfaction in using public sector services through the policies, decrees, and law.